Liquid phase deposition of TiO2 thin films: influence of annealing temperature on ultraviolet response - Ali Shirpay (Discover Applied Sciences)
Abstract In this study, titanium oxide (TiO2) thin films were initially synthesized on a glass substrates using the liquid phase deposition (LPD) method. The simple technique demonstrated the capability to control film thickness at the nanoscale. However, single-step deposition did not yield uniform films, so two-step deposition process was employed to achieve uniformity. The resulting TiO₂ thin films were subsequently annealed at various temperatures (450 °C, 550 °C, and 650 °C). The TiO2 thin films were characterized by XRD, FE-SEM, UV–Vis spectroscopy, and UV photoresponse measurements. Their ultraviolet (UV) photoresponse was investigated following annealing. XRD patterns confirmed the formation of TiO₂, while FE-SEM images revealed that the thin films produced via the two-step LPD method exhibited a nearly uniform distribution of TiO₂ particles. Cross-sectional FE-SEM analysis indicated that the film thickness was approximately 500 nm. UV–Vis spectroscopy and Urbach energy analysis showed that annealing temperature had minimal impact on both the energy band gap (ranging from 4.1 to 4.13 eV) and the Urbach energy. Additionally, the UV photoresponse results demonstrated that the TiO₂ thin film annealed at 550 °C exhibited superior performance compared to the others, with a response of 9.99 mA/W, quantum efficiency of 34.02%, and sensitivity of 9.92.